2013
DOI: 10.1021/ac401752j
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Analysis of Biological Reactions Based on Heterogeneous Assays in Liquid Plugs of Nanoliter Volume

Abstract: In this article, we present a concept which uses liquid plugs as reaction volumes for heterogeneous assay reactions to facilitate time-resolved analysis of biomolecular reactions. For this purpose, the reaction is first compartmentalized to a train of many identical plugs. Therefore, we established a simple fluidic setup build from off-the-shelf available tubing and connectors. It permits reliable formation of plugs and successive dosing of further assay reagents to these compartments (plug volume <5% CV). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Fluorescent RNA aptamers have also been used as an alternative simple strategy for monitoring RNA in real-time (Chizzolini et al 2014). High-throughput analysis of biomolecular interactions can also be performed by encapsulating CFPS reactions into nanoliter droplets and examining interactions via an immunoassay (Rendl et al 2013). Additionally, HPLC analyses for monitoring metabolite concentrations are straightforward to use because CFPS reactions can be run directly on an HLPC or MS machine.…”
Section: Implementing Genetic Network In Vitromentioning
confidence: 99%
“…Fluorescent RNA aptamers have also been used as an alternative simple strategy for monitoring RNA in real-time (Chizzolini et al 2014). High-throughput analysis of biomolecular interactions can also be performed by encapsulating CFPS reactions into nanoliter droplets and examining interactions via an immunoassay (Rendl et al 2013). Additionally, HPLC analyses for monitoring metabolite concentrations are straightforward to use because CFPS reactions can be run directly on an HLPC or MS machine.…”
Section: Implementing Genetic Network In Vitromentioning
confidence: 99%
“…CF-synbio expands the available tools for in situ monitoring beyond fluorescent protein expression. Examples include bioluminescence, FRET, and aptamer-based binding assays [46,47]. One elegant approach made possible by CF was recently demonstrated by Rendl and coworkers, who employed microfluidic reactors with the capability of online real-time sandwich tagging assays [47].…”
Section: Monitormentioning
confidence: 99%
“…Examples include bioluminescence, FRET, and aptamer-based binding assays [46,47]. One elegant approach made possible by CF was recently demonstrated by Rendl and coworkers, who employed microfluidic reactors with the capability of online real-time sandwich tagging assays [47]. Similar to in vivo, in situ monitoring of CF systems relies heavily on spectrophotometry.…”
Section: Monitormentioning
confidence: 99%
See 1 more Smart Citation
“…Jishan13 et al used gold nanoparticle aggregates for highly sensitive identification of single-nucleotide polymorphisms in a mutated target at a concentration as low as 70 fM. Daniel et al introduced ultra-small volume analysis, ranging from micro- to nanoliters1415161718. Xueen et al demonstrated micro-loop-mediated isothermal amplification (μLAMP) with a sample volume of 0.4 μL under isothermal conditions (63°C) in 201019.…”
mentioning
confidence: 99%